PERUBAHAN DALAM TRADISI PETUNG WETON MASYARAKAT JAWA (Studi tentang Penentuan Hari Pernikahan di Desa Rambah Muda Kecamatan Rambah Hilir Kabupaten Rokan Hulu) - Hesti Eka Rahmawati; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The petung weton tradition is a tradition to determine a person’s wedding day by calculating the date of birth of the birth and groom. The people of Rambah Muda village believe that by using this tradition, the event that will be held will get good luck and the sustenance of the bride and groom will be launched, but nowadays the petung weton tradition is rarely used and there are changes. The purpose of this study: 1) To find out the differences that occur in the tradition of petung weton carried out in the past and present. 2) To find out the causes of changes in the petung weton tradition in the Javanese community in Rambah Muda village. The study used qualitative research methods. The theory used is William F.Ogburn’s Theory of social change. In this case the determination of information using a purposive sampling technique that has been determined previously. The study found that the petung weton tradition is a hereditary tradition that is still practiced today. This tradition is carried out to determine the wedding day by the Javanese people with various traditional processions. The implementation is deliberation by both the families of the prospective groom and bride, fasting the day and making offerings that are placed in various places such as in the kitchen, bridal room, party tent, and others. This tradition already exists in Rambah Muda village and began to be implemented in the 1990s. Changes that occur in the petung weton tradition are caused by several things, such as technological advences and the times, higher education levels and increasingly diverse villagers. Keywords: petung weton, culture, change.